"If Their Face Starts Turning Purple, You Are Probably Doing Something Wrong": Young Men's Experiences with Choking During Sex. Issue 5 (1st July 2022) - Herbenick, Debby; Guerra-Reyes, Lucia; Patterson, Callie; Rosenstock Gonzalez, Yael R.; Wagner, Caroline; Zounlome, Nelson O. O.
Abstract: Choking/strangulation during sex has become prevalent in the United States. Yet, no qualitative research has addressed men's choking experiences. Through interviews with 21 young adult men, we examined the language men use to refer to choking, how they first learned about it, their experiences with choking, and consent and safety practices. Men learned about choking during adolescence from pornography, partners, friends, and mainstream media. They engaged in choking to be kinky, adventurous, and to please partners. While many enjoyed or felt neutral about choking, others were reluctant to choke or be choked. Safety and verbal/non-verbal consent practices varied widely.